The Effect of Financial Distress, Audit Committee, Auditor Switching, and Industry Types on Audit Delay in the Covid-19 Pandemic of Companies Listed on the Indonesian Stock Exchange’s KOMPAS100 Index - Sumajow, Kezia Cicilia; Kalangi, Lintje; Weku, Priscillia (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2022)
Audit delay is a phenomenon that remains to occur every year. This study aims to determine the influence of financial distress, audit committee, auditor switching, and industry types upon audit delay the Indonesian Stock Exchange’s KOMPAS100 Index. This study used a quantitative approach. The sample was selected and obtained by the simple random sampling method from 72 companies successively listed in the Indonesian Stock Exchange’s KOMPAS100 index during 2020. The analytical was multiple linear regression. The data analysis was descriptive and multiple linear regression methods. The results indicate that audit committee and auditor switching does not affect audit delay. Financial distress and industry types have a significant positive effect on audit delay.